Pengaruh Kualitas Pelayanan Fasilitas dan Harga Terhadap Kepuasan Konsumen di Hotel Bina Darma Palembang - Nur Hidayah; Andrian Noviardy (Publikasi Indonesia, 2022)
The formulation of the problem in this study is whether service quality affects customer satisfaction at Hotel Bina Darma Palembang Does facilities affect customer satisfaction at Hotel Bina Darma Palembang Does price affect customer satisfaction at Hotel Bina Darma Palembang Does service quality, facilities and prices affect customer satisfaction Hotel Bina Dharma Palembang. This aims to find out what affects the quality of service facilities and prices to consumers. The location of this research is located at Jln Jend A Yani 9/10 Ulu Palembang City. The population that has been used by researchers is some visitors who are at the Hotel Bina Darma Palembang which has a total of 5,561 visitors. The number of samples that have been obtained and calculated has a total of 98 respondents. The data collection technique in this study was a questionnaire. The hypothesis test used in this study is the t and f test. The results of this study indicate that the condition of service quality, facilities and prices affect consumer satisfaction.